The Culture Shock Phenomenon of Overseas Students at IPB University Vocational School - Habibie, Muhamad; Nugroho, David Rizar; Suparman, Suparman; Manisya, Nabhila; Khairunnisa, Anggi Widia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study explores the effectiveness of the collaboration between Samsung and Blackpink in enhancing Samsung’s brand image among young users. In the digital era, celebrity collaboration has become an important strategy for building brand image through social media. Using a quantitative approach, data were collected through a survey questionnaire distributed to Blackpink fans to understand their perceptions of this campaign. The study results indicate that the collaboration successfully strengthens emotional engagement, increases interest in Samsung products, and reinforces the brand’s image as a modern, relevant brand. Using the EPIC Model, variables such as Empathy and Persuasion were found to significantly impact the creation of a positive brand image. Furthermore, the collaboration effectively enhances Samsung’s uniqueness and brand value in the eyes of consumers, who view Samsung as an innovative and trend-following brand. These findings suggest that celebrity collaboration strategies are effective for building a strong brand image, particularly on social media, and can serve as a reference for other companies looking to leverage celebrity influence to achieve similar goals. The study also highlights the vital role of social media in expanding brand reach, fostering engagement, and enhancing consumer loyalty through a more personal approach. In an era where social media significantly influences consumer behavior, this collaboration proves that strong emotional connections with consumers are key to brand success.